2017
DOI: 10.3389/fphar.2017.00538
|View full text |Cite
|
Sign up to set email alerts
|

Tamarixinin A Alleviates Joint Destruction of Rheumatoid Arthritis by Blockade of MAPK and NF-κB Activation

Abstract: Background: Tamarixinin A, a natural tannin isolated from Myricaria bracteata, has been confirmed to have moderate anti-inflammatory effects in vitro and in vivo. However, how it effects rheumatoid arthritis (RA) is still unknown. Therefore, the aim of this study is to investigate the therapeutic effects of tamarixinin A on experimental RA, and explore the underlying mechanism.Methods: The anti-arthritic effects of tamarixinin A were evaluated on collagen-induced arthritis (CIA) mice and adjuvant-induced arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells. [29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells. [29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that synovial inflammatory cells were significantly decreased after the anti-TNF-α mAb treatment, suggesting that TNFα played an important role in RA pathogenesis [37][38][39]. e key pathogenesis of RA was overexpressed inflammatory cytokines and tissue injury mediated by persistent NFkappa B activation, and agents could alleviate RA phenotype by blockade of NF-kappa B activation [40,41]. Recent work indicated that the insufficient apoptosis of inflammatory cells in the RA joint might contribute to pathogenesis, and induction of inflammatory cells apoptosis is a feasible strategy for treating RA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast-like synoviocytes (FLSs), which can be cancerous and can destroy cartilage, participate in synovitis, are the main effectors of bone destruction in RA. The raised invasiveness of these cells is closely related to the pathogenesis and progression of RA (Zhuang et al 2017). Numerous studies have shown that FLSs in RA patients can abnormally produce high levels of matrix metalloproteinases (MMPs), which are important effector molecules of bone destruction (Huang et al 2017).…”
Section: Introductionmentioning
confidence: 99%